2009
DOI: 10.4161/cbt.8.22.9880
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 upregulates expression of TRF2 and TRF2 inhibition reduces tumorigenesis in human colorectal carcinoma cells

Abstract: Overexpression of TRF2 protein was detected in SW480 cells and 19 of 39 colorectal carcinoma tissues (49%), no overexpression was observed in 21 of 21 adjacent peritumoral normal colorectal tissues. After siRNA silencing TRF2 expression, the proliferation and colony formation of SW480 cells were significantly inhibited. Defective TRF2 induced apoptosis and increased chromosomal instability in SW480 cells, in which there were more end-to-end fusions and ring chromosomes. Chip assay and EMSA showed that transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 23 publications
4
26
0
Order By: Relevance
“…Since TRF2 is an important element of telomere homeostasis and loss of TRF2 yields end-to-end fusions, telomere shortening, activation of DNA damage pathways, TRF2 regulation could be a contributing factor in cancer progression [4]. In accordance with this hypothesis, TRF2 overexpression is detected in various tumor types like gastric carcinoma, hepato-carcinogenesis or colorectal carcinoma [8][9][10]. Regulation of TRF2 expression was found to be correlated with tumor grade in lung cancer progression [11].…”
Section: Introductionsupporting
confidence: 60%
“…Since TRF2 is an important element of telomere homeostasis and loss of TRF2 yields end-to-end fusions, telomere shortening, activation of DNA damage pathways, TRF2 regulation could be a contributing factor in cancer progression [4]. In accordance with this hypothesis, TRF2 overexpression is detected in various tumor types like gastric carcinoma, hepato-carcinogenesis or colorectal carcinoma [8][9][10]. Regulation of TRF2 expression was found to be correlated with tumor grade in lung cancer progression [11].…”
Section: Introductionsupporting
confidence: 60%
“…Sp1 is a member of the gene family with sequence-specific DNA-binding C-terminal zinc-finger motifs. It plays a critical role in the regulation of expression of mammalian genes lacking a TATA box by binding to GC/GT boxes to activate transcription (Raynaud et al, 2008;Dong et al, 2009). It has been reported that Sp1 is involved in the development and progression of several types of cancers, including colorectal cancer (Dong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It plays a critical role in the regulation of expression of mammalian genes lacking a TATA box by binding to GC/GT boxes to activate transcription (Raynaud et al, 2008;Dong et al, 2009). It has been reported that Sp1 is involved in the development and progression of several types of cancers, including colorectal cancer (Dong et al, 2009). At present, CCND1, PDEGF, p21, VEGF, TGFβ, E2F1, c-fos, OPN, and TGFα are the cancer-related Sp1 targets that have been identified (Gartel et al, 2000;Zhu et al, 2002;Takami et al, 2007;Dong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telomere repeat binding factor 2 (TRF2) plays a key role in the protective activity of telomere and is overexpression in CRC. Study showed transcription factor Sp1 is also involved in upregulation of TRF2, that is, TRF2 is overexpressed in CRC mediated by Sp1 regulation (Dong et al, 2009).…”
Section: Discussionmentioning
confidence: 99%